Prognosis of Placental Insufficiency in Pregnant Women Treated for Coronavirus - Haydarova Nigora Bahodirovna (Genius Journals, 2023)
The aim of the scientists' research is to optimize the treatment of pregnant women with a moderate form of a new coronavirus infection by including a sorbent in complex therapy
Keywords: Women; prognosis; pregnant women